Effect of methanol extract of Jatropha macrantha Müll. Arg. in rat erectile dysfunction - Tinco, Aldo (2011)
Objectives: To determine the effect of Jatropha macrantha Müll. Arg 'huanarpo macho' methanol extract in rats with induced erectiledysfunction. Design: Experimental. Setting: Pharmacology Laboratory, Faculty of Medicine, Universidad Nacional Mayor de San Marcos,Lima, Peru; Pharmacy Laboratory, Universidad Nacional de San Cristobal de Huamanga, Ayacucho, Peru. Biological material:Plant collected from Ayacucho, wistar male rats 300+/-50 g. Interventions: Plant collection was done in Vilcas Huaman Province - Ayacucho.Sexual behavior, nitric oxide concentration and vasorelaxant effect were determined in isolated rats penis corpus cavernosumdistributed in the following groups: group 1 water 10 mL/kg, group 2 sildenafil 5 mg/kg, groups 3, 4 and 5 respectively methanol extract100, 200 and 300 mg/kg. Organs were isolated in groups receiving 50, 100 and 300 ug/mL of extract, L-arginine 300 uM, 30 um acetylcholine,epinephrine u/mL and sildenafil (3,2 × 10-5 mg/mL). Main outcome measures: Flavonoids isolated, sexual behavior of rats, nitricoxide plasma levels, and cavernous smooth muscle relaxation. Results: By chromatography flavones-like structures were revealed, andby UV spectroscopy and displacement reactions 6-hydroxy-4’,5,7-trimethoxy-flavone, 4’,7-dihydroxy-5,6-dimethoxi-flavone, 7-hydroxy-3’,4’,5’,5,8-pentamethoxyflavone, 4’,7-dihydroxy-3’,5,6-trimethoxy-flavone, and LD50 1357 mg/kg were identified. Sexual behavior wasdose-dependent; oral administration of 300 mg/kg of plant increased frequency of mounts in 75% and raised levels of nitric oxide 85%,while 200 mg/kg dose, mounts were respectively 71.1% and 32.4% (p <0.05). Conclusions: Jatropha macrantha Müll Arg ‘huanarpo macho’methanolic extract had vasorelaxant modulating effect in rats with induced erectile dysfunction with nitric oxide levels increase.